Corporate sustainability and the market pricing of accounting numbers. (5th January 2021) - Choi, Hyunjung; Moon, Doocheol; Guiral, Andres; Choi, Byungchul
Abstract: This study investigates the association between CSR and the market pricing of accounting income numbers' persistence. More specifically, we examine whether the market evaluation of earnings persistence relies on the firm's CSR activities. We find that the market overestimates the persistence of earnings, leading the market to overprice the earnings for CSR companies in Korean setting. We also find that market overprices components of earnings, which are accruals and cash flow from operations, for CSR companies. However, results show that the level of CSR activities does not affect investors' rational pricing of earnings. This study suggests that market participants prefer companies engaging in CSR activities because they are more likely to provide better financial performance and earnings quality. This preference leads investors to overestimate the persistence of earnings and its components for CSR companies.